Monitoring detention, custody, torture and ill-treatment: a practical approach to prevention and documentation - Payne-James, Jason (CRC Press, 2018)
International legal framework on torture / Juan E. Méndez -- The role and responsibilities of health professionals involved in the care of those in detention / Jørgen L. Thomsen -- Standards applicable in the prevention of torture in places of detention / Jonathan Beynon -- Healthcare for those in detention / Michael Levy -- Psychological assessment and documentation of torture in detention / Nimisha Patel -- Assessment of physical evidence of torture or cruel, inhuman and degrading treatment during visits to places of detention / Jason Payne-James, Jonathan Beynon, and Duarte Nuno Vieira -- Radiology in the documentation of torture and ill-treatment / Hermann Vogel -- Management of hunger strikes in detention / Hernán Reyes -- Legal aspects of detention in military detention / Kirsty Sutherland and Peter Glenser -- Sexual assault in detention / Jason Payne-James -- Children in detention / Peter Green -- Investigation of ill-treatment during detention / Hernán Reyes -- Investigation of deaths in custody / Marc Bollman, Morris Tidball-Binz, Bernice Elger, and Patrice Mangin -- The Istanbul Protocol : development, practical application, and future directions / Vincent Iacopino -- Dilemmas for healthcare professionals involved in the care of detainees / Máximo Alberto Duque Piedrahíta -- Solitary confinement : current concerns and proposed protections / Sharon Shalev